2021
DOI: 10.1121/10.0002971
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of room acoustics coupling in Hagia Sophia of İstanbul for its different states

Abstract: _ Istanbul's Hagia Sophia is a monumental structure with multiple sub-spaces coupled to one another through arches. Its architectural elements have undergone alterations as its function has changed from that of a church to a mosque, a mosque to a museum, and back to a mosque. This study makes use of Hagia Sophia's rich formal and material characteristics to conduct a comprehensive investigation of room acoustics coupling. The methodology involves the application of the diffusion equation model (DEM) for sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Another study used scaled-down physical models of a reverberant chamber to investigate how sound-absorbing materials such as curtains should be modelled in geometrical acoustic software when hung freely in ancient churches [58]. In a comprehensive investigation of room acoustics coupling, Hagia Sophia's rich formal and material characteristics were examined [79]. Other studies have shown that fabric sound absorbers and Buddha statues installed in the main hall have an obvious influences on the sound field of Buddhist temples [50].…”
Section: Sound Fieldmentioning
confidence: 99%
“…Another study used scaled-down physical models of a reverberant chamber to investigate how sound-absorbing materials such as curtains should be modelled in geometrical acoustic software when hung freely in ancient churches [58]. In a comprehensive investigation of room acoustics coupling, Hagia Sophia's rich formal and material characteristics were examined [79]. Other studies have shown that fabric sound absorbers and Buddha statues installed in the main hall have an obvious influences on the sound field of Buddhist temples [50].…”
Section: Sound Fieldmentioning
confidence: 99%
“…Sü Gül [27] conducted in situ tests in Hagia Sophia of Istanbul in Turkey and particularly simulated the exhibition states with a marble floor. The volume of each individual space ranged from 625 to 95,960 m 3 .…”
Section: Museums/exhibition Spacesmentioning
confidence: 99%
“…The acoustic simulations of heritage spaces enable the knowledge thereof to be revealed and their sound architecture to be preserved [28][29][30][31][32], given that the quality of the documentary and graphic information employed to create the model determines the accuracy of the prediction. In digital acoustic modeling, the details are simplified to improve the approximation; when studying the acoustics of historical-cultural buildings, however, the effect of architectural detail can prove to be of major importance [10].…”
Section: Introduction and Goalsmentioning
confidence: 99%